LEARNING STYLES AND STRATEGIES AMONG HIGH SCHOOL STUDENTS - Ismoilova Shodiya; Dilnoza Kamolova (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This research investigates the learning styles and learning strategies of high school students at School No. 13 in Fergana, Uzbekistan. The goal is to understand how students prefer to learn and what techniques they use to study. The study used questionnaires to gather data from 120 students, focusing on four learning styles (Visual, Auditory, Reading/Writing, and Kinesthetic) and three types of strategies (Cognitive, Metacognitive, and Socio-affective). The results showed that most students prefer visual and auditory learning styles. A strong connection was found between learning styles and the learning strategies students use. These findings can help teachers create better, more personalized teaching methods.